New Formations in Circulation Areas and Technology - Canbakal Ataoğlu, Nihan (ICONARCH International Congress of Architecture and Planning, 2012)
In the post-modem period, in today' s architecture, spectacular and dramatic changes are observed in the formation of buildings and the organization of interior space. Even though these dramatic changes draw attention in the forms of structures at first glance, when interior space organizations and circulation areas are analyzed, radical changes are identified in design strategies, scale, geometry, perception, and size of circulation spaces. Circulation spaces of today, which take form around large and complex atriums, are designed with ramps, bridges, transparent elevators, stairs, escalators, and take shape with expressions of speed and dynamism which reflect spirit of the age. These new, exciting, interesting, surprising and dynamic circulation areas, which offer experiences very different from ordinary circulation areas designed with the traditional and conventional concept, take nourishment from computer technologies, new materials, new structures and new technologies.